Sirolimus Treatment of an Infant With Intrathoracic Kaposiform Hemangioendothelioma Complicated by Life-threatening Pleural and Pericardial Effusions. Issue 1 (January 2020) - Duan, Lucy; Renzi, Samuele; Weidman, Danielle; Waespe, Nicolas; Chami, Rose; Manson, David; Cada, Michaela; Carcao, Manuel
Abstract : Kaposiform hemangioendothelioma (KHE) is a rare infiltrative vascular tumor that may be associated with Kasabach-Merritt Phenomenon (KMP), which is a consumptive coagulopathy with potentially life-threatening thrombocytopenia. Management of KHE and KMP is challenging, and currently, there are no standardized validated treatment protocols. Mammalian target of rapamycin inhibitors have been shown to be effective in the treatment of KHE. We describe a term male who presented as a diagnostic dilemma with life-threatening pleural and pericardial effusions and severe thrombocytopenia. After extensive work-up the etiology for his condition was determined to be KHE with KMP. The patient was commenced on sirolimus and responded well to therapy with resolution of KMP.